On (1,2)^⋆-g ̆-closed and open functions - R. Asokan , O. Nethaji, A. Ponmalar , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Main aim of this paper, we introduce and study the concepts of functions namely (1,2)⋆-